Increased Expression of LASI lncRNA Regulates the Cigarette Smoke and COPD Associated Airway Inflammation and Mucous Cell Hyperplasia - Manevski, Marko; Devadoss, Dinesh; Long, Christopher; Singh, Shashi P.; Nasser, Mohd Wasim; Borchert, Glen M.; Nair, Madhavan N.; Rahman, Irfan; Sopori, Mohan; Chand, Hitendra S. (Frontiers in Immunology, 2022)
Rationale: Cigarette smoke (CS) exposure is most common risk factor for chronic obstructive pulmonary disease (COPD). In conducting airways, CS disrupts airway epithelial functions, mucociliary clearances, and innate immune responses that are primarily orchestrated by human bronchial epithelial cells (HBECs). Mucus hypersecretion and dysregulated immune response are the hallmarks of chronic bronchitis (CB) that is often exacerbated by CS. Notably, we recently identified a long noncoding RNA (lncRNA) antisense to ICAM-1 (LASI) that mediates airway epithelial responses. Objective: To investigate the role of LASI lncRNA in CS-induced airway inflammation and mucin hyperexpression in an animal model of COPD, and in HBECs and lung tissues from former smokers with and without COPD. To interrogate LASI lncRNA role in CS-mediated airway mucoinflammatory responses by targeted gene silencing. Methods: Small airway tissue sections from cynomolgus macaques exposed to long-term mainstream CS, and those from former smokers with and without COPD were analyzed. The structured-illumination imaging, RNA fluorescence in-situ hybridization (FISH), and qRT-PCR were used to characterize lncRNA expression and the expression of inflammatory factors and airway mucins in a cell culture model of CS extract (CSE) exposure using HBECs from COPD (CHBEs) in comparison with cells from normal control (NHBEs) subjects. The protein levels of mucin MUC5AC, and inflammatory factors ICAM-1, and IL-6 were determined using specific ELISAs. RNA silencing was used to block LASI lncRNA expression and lentivirus encoding LASI lncRNA was used to achieve LASI overexpression (LASI-OE). Results: Compared to controls, LASI lncRNA was upregulated in CS-exposed macaques and in COPD smoker airways, correlating with mucus hyperexpression and mucus cell hyperplasia in severe COPD airways. At baseline, the unstimulated COPD HBECs (CHBEs) showed increased LASI lncRNA expression with higher expression of secretory mucin MUC5AC, and inflammatory factors, ICAM-1, and IL-6 compared to no-COPD HBECs (NHBEs). CS extract (CSE) exposure of CHBEs resulted in augmented inflammation and mucus expression compared to controls. While RNA silencing-mediated LASI knockdown suppressed the mucoinflammatory response, cells overexpressing LASI lncRNA showed elevated mRNA levels of inflammatory factors. Conclusions: Altogether, LASI lncRNA may represent a novel target to control the smoke-mediated dysregulation in airway responses and COPD exacerbations.